SUPLEMENTAÇÃO DE ÃCIDO ASCÃ“RBICO NA ALIMENTAÇÃO DE Bombyx mori L. (LEPIDOPTERA: BOMBYCIDAE) - Miranda, José Ednilson; Takashi, Roque; Silva, Alessandra F. da (REVISTA DE AGRICULTURA, 2015)
SUPLEMENTAÇÃO DE ÃCIDO ASCÃ“RBICO NA ALIMENTAÇÃO DE Bombyx mori L. (LEPIDOPTERA: BOMBYCIDAE)